Retail Atmospherics and In-Store Nonverbal Cues: An Introduction - Grewal, D; Roggeveen, A; Puccinelli, N; Spence, C (Wiley-Liss Inc., 2014)
Customers' in-store experiences are having a profound impact on their shopping behavior. In this special issue, two key variables are highlighted: the retail environment and role of nonverbal cues. The eight papers in this special issue present numerous cutting edge issues in these two research domains. Each of these papers and some of their salient contributions are briefly overviewed in this introductory editorial. The goal of this special issue (and the articles in it) is to serve as an impetus for additional research. © 2014 Wiley Periodicals, Inc.